Counseling Mental Health Problems In School-Age Children - Sukma ayu candra Kirana; Dya Sustrami; Lela Nurlela; Hidayatus Syadiah; Diyan Mutyah; A.V Sri Suhardiningsih; Dini Mei Widayanti; Dhian Satya Rachmawati; Yoga Kertapati (UNUSA Press, 2026)
Background, Mental health of school-age children will be achieved by individuals who are able to develop physically, intellectually, and emotionally. However, because of the magnitude of infectious diseases that occur, mental health problems are not too taken into account. School-age children who have mental health problems like vulnerable emotional and behavior in the functioning of daily life, even experiencing difficulties in learning and socialization functions. The problem is often not responded to in time so that school-age children come to the consultation in conditions that are quite severe and require appropriate treatment. The purpose of this activity is to improve students ' knowledge related to mental health problems in school-age children. Methods, Community service consists of three stages, Education, Student Assistance and ended by the evaluation of health education activities on mental health problems in school-age children at SD Muhammadiyah 9 Surabaya. These activities involve the head of School, teachers and students. Results and discussion, the results of posttest conducted obtained 78% of participants were able to correctly answer questions about mental health problems in school-age children. Conclusion, it is expected that school students can become the successors of the nation who have an understanding and knowledge of mental health problems in school-age children in order to form self-awareness of the understanding and knowledge that has been obtained by students.